UMBILICAL PILONIDAL SINUS - Mustafa, Ghulam; Akber, Ghulam; Lodhi, Junaid Khan; Mutahir, Muhammad; Malik, Asim (Journal of Ayub Medical College Abbottabad, 2014)
A pilonidal sinus is a blind-end tract lined with granulation tissue, which leads to a cystic cavity lined with epithelial tissue. As the name suggests, these hair containing abscesses are usually found in the sacro-coccygeal region. However, they may also occasionally occur in the axilla, groin, inter-digital web, umbilicus, nose, inter-mammary areas, supra-pubic area, clitoris, prepuce, penis, occiput, and on the feet. Sinus is caused by the friction of the skin at the base of the spine, leading to the embedding of the hair beneath the surface. The hair forms small cavities or pits, which are in truth, enlarged hair follicles, which go on to become sinuses. Bacteria and debris enter this sterile area, producing local inflammation and formation of pus-filled abscesses. In chronic condition, the sinus becomes an open cavity, constantly draining small amounts of fluid. In this case report we present a case of umbilical pilonidal sinus in a young boy. Keywords: Pilonidal sinus, umbilicus, sinus, omphalectomy